Analisis Tumbukan Fisika pada Tabrakan Mobil Menggunakan Software BeamNG.drive - Fachri Ramdhan; Ahmad Faizal Yus'an; Bayu Setiaji (Jurnal Teori dan Aplikasi Fisika, 2025)
This study aims to examine the phenomenon of collision between two vehicles by observing the changes in momentum, kinetic energy, and vehicle deformation as a response to the collision, as well as evaluating the accuracy of the simulation using BeamNG.drive software by comparing it to the applicable physical theories in collisions. The research method used is experimental by conducting collision simulations using BeamNG.drive software. The initial velocity variations of the colliding vehicle (car A) are set at 50, 75, and 100 km/h, while the struck vehicle (car B) is in a stationary condition. The analysis is carried out by calculating the conservation of momentum, kinetic energy, and the coefficient of restitution of the collision. The results show that the initial and final momentum values of the system are almost the same, in accordance with the principle of conservation of momentum. However, there is a significant decrease in kinetic energy values, indicating an inelastic collision where kinetic energy is transformed into deformation energy. The very low coefficient of restitution values (approaching 0) also confirm the nature of the inelastic collision. The simulation results using BeamNG.drive are consistent with the relevant physical theories on collisions, demonstrating the accuracy of the software in modeling vehicle collision phenomena. Keywords: collision, momentum conservation, kinetic energy, coefficient of restitution, Beam.